Sound Horeg as Political Campaign Strategy in the Banyuwangi Local Election - Aditya Firman Saputra; Randy Prasetyo (PT Pro Panoramic Solution, 2026)
The phenomenon of sound horeg in the 2024–2029 Banyuwangi local election reflects a significant transformation in local political campaign strategies that integrate popular culture, grassroots entertainment, and emotional political communication. Originally functioning as a form of rural entertainment, sound horeg has evolved into a strategic political medium capable of mobilizing mass participation, fostering emotional attachment, and strengthening cultural identification between candidates and voters. This study aims to analyze the role of sound horeg as a political campaign strategy, the political communication processes involved, and its implications for voter perceptions, cultural identity, and democratic quality. This research employs a qualitative case study approach, utilizing in-depth interviews with campaign teams, local political actors, sound horeg community members, religious figures, and voters, complemented by participant observation and document analysis. The analytical framework integrates Harold Lasswell’s political communication model, Antonio Gramsci’s theory of cultural hegemony, Ernesto Laclau’s theory of populism, and perspectives from cultural sociology and the sociology of religion. The findings reveal that sound horeg functions not merely as entertainment but as a symbolic cultural practice that produces political legitimacy, emotional mobilization, and populist identification. However, the strategy also raises ethical concerns regarding the commodification of culture, the dominance of emotional appeals over policy discourse, and the potential exclusion of certain social groups. This study contributes to the literature on local political communication by demonstrating how culture, religion, and power intersect in contemporary Indonesian local elections